Olympic Study and Mega Events. A Study of Sport cricket History from 1977 to 2013 for peace between India and Pakistan. Sports as a tool for peace development - Shahid, Shakeel Ahmad (Πανεπιστήμιο Πελοποννήσου, 2012)
Was cricket diplomacy between India and Pakistan been successful? That is the point for this thesis. The man appointed special envoy by Pakistan Prime Minister Nawaz Sharif to improve relations with India also narrowed down a three-pronged strategy for revival of ties between the two sub-continental neighbours.The aims of this work is three-pronged. First, it discusses the connection between sport and politics, and the relationship between sport and diplomacy. Second, it situates the case of cricket diplomacy in relation to other cases of sport diplomacy. And, finally, it identifies and discusses the particularities of the relationship between India and Pakistan and cricket diplomacy. Sport’s potential for peace has achieved an increasing amount of attention in recent years. It is considered as having ‘the power to bring people together, bridge differences, and promote communication and understanding,’ and not the least contribute to ‘lasting peace,’ in the United Nations Secretary-General’s 2006 report Sport for Development and Peace: the way forward. Sport then, or certain sports such as cricket at certain times, clearly has a significant place in contemporary social life. Cricket is a sport that permeates practically every layer of South Asian societies, and the game has occupied ‘a central place in a range of emerging positions and identities’ in the years after the countries achieved independence in the late 1940s. The term cricket diplomacy was born in 1987 as President of Islamic Republic of Pakistan’s Zia-ul-Haq launches “cricket diplomacy” by watching a cricket Test match between India and Pakistan with then Indian Prime minister Rajiv Gandhi, defusing tension as both countries mass troops on their borders. Sports diplomacy describes the use of sport as a means to influence diplomatic, social, and political relations. Experts suggest that sports diplomacy may transcend cultural differences and bring people together. In a statement 9 on 18 July 2012 at Islamabad, Pakistan President Asif Ali Zardari referred to the resumption of cricketing ties with India as a formidable confidence building measure and a way forward to encouraging people-to-people contact for Peace.
Keywords: Olympics - Philosophy; Cricket - India; Diplomacy; Ολυμπιακοί αγώνες - Φιλοσοφία; Κρίκετ - Ινδία; Διπλωματία; Olympic Idea; Cricket; India; Pakistan; Peace; Diplomacy; Ολυμπιακή Ιδέα; Κρίκετ; Ινδία; Πακιστάν; Ειρήνη; Διπλωματία